Application of Islamic Cultural-Historical Values in Developing the Character of Learners in Islamic Elementary School - Khusnul Khotimah; Ade Mukhlis Supandi; Sutrisno Sutrisno (Nazhruna: Jurnal Pendidikan Islam, 2022)
This article is motivated by the presence of the character of students during the pandemic, this is due to the lack of interaction of students with teachers which causes character education to be less conveyed. Teachers as the front line in education need to have and develop strategies and methods in learning so that targeted learning can be achieved. This writing intends to find out why Islamic cultural history education has not been able to fully develop the character of students, and how to instill cultural-historical values ​​in developing the character of students during the covid-19 pandemic. This type of research is field research with a qualitative approach. The data in this study were obtained from direct observations, interviews, and literature studies based on previous research articles. Then the data is collected and analyzed to obtain the nature of the cultivation of these character values. The results of this article indicate that Islamic cultural history education has not been able to fully develop the character of students because the material taught is not by the age of student growth, and the application of historical values ​​of Islamic culture to develop the character of students is through exemplary and habituation methods. These examples were obtained from studying the history of the Messenger of Allah during his preaching with his companions (Khulufaurrasyidin).